2022
DOI: 10.1186/s40364-022-00418-9
|View full text |Cite
|
Sign up to set email alerts
|

The Wnt/β-catenin signalling pathway in Haematological Neoplasms

Abstract: Leukaemia and lymphoma are common malignancies. The Wnt pathway is a complex network of proteins regulating cell proliferation and differentiation, as well as cancer development, and is divided into the Wnt/β-catenin signalling pathway (the canonical Wnt signalling pathway) and the noncanonical Wnt signalling pathway. The Wnt/β-catenin signalling pathway is highly conserved evolutionarily, and activation or inhibition of either of the pathways may lead to cancer development and progression. The aim of this rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 122 publications
1
6
0
Order By: Relevance
“…Wnt/ β-catenin signaling pathway dysregulation is the tipping point in tumor progression, invasion, and metastasis via its effect on β-catenin and Cyclin D1. (21) Concerning β-catenin results in the present study, immunopositivity was found in normal oral epithelium with membranous expression in all epithelial cell layers. These findings were consistent with previous study that found β-catenin expression was detected only in the cytoplasmic membrane of the normal oral mucosa.…”
Section: Discussionsupporting
confidence: 41%
“…Wnt/ β-catenin signaling pathway dysregulation is the tipping point in tumor progression, invasion, and metastasis via its effect on β-catenin and Cyclin D1. (21) Concerning β-catenin results in the present study, immunopositivity was found in normal oral epithelium with membranous expression in all epithelial cell layers. These findings were consistent with previous study that found β-catenin expression was detected only in the cytoplasmic membrane of the normal oral mucosa.…”
Section: Discussionsupporting
confidence: 41%
“…On the other hand, the dysregulation of the Wnt/β-catenin pathway is often associated with a variety of diseases, including cancer [ 62 , 63 ]. In colorectal cancers, the Wnt/β-catenin pathway is one of the most important signaling pathways [ 64 ]; therefore, the Wnt/β-catenin signaling pathway is an attractive target for cancer treatment and several small inhibitors targeting the Wnt/β-catenin pathway have been examined in preclinical and clinical studies [ 65 , 66 , 67 ]. In addition, some studies have indicated that chalcones are also capable of acting on this signaling pathway.…”
Section: Molecular and Cellular Mechanisms Of Actionmentioning
confidence: 99%
“…The increase in BALP and PINP indirectly reflects the increase in bone loss, and the change in clinical bone metabolic index occurs half a year earlier than bone density, so it is suitable for short-term observation indexes. Therefore, these two indexes can be used as reference indexes for the diagnosis and evaluation of curative effects after treatment [32][33][34].…”
Section: Discussionmentioning
confidence: 99%